2007
DOI: 10.1038/nature06266
|View full text |Cite
|
Sign up to set email alerts
|

Portability of paddle motif function and pharmacology in voltage sensors

Abstract: Voltage-sensing domains enable membrane proteins to sense and react to changes in membrane voltage. Although identifiable S1-S4 voltage-sensing domains are found in an array of conventional ion channels and in other membrane proteins that lack pore domains, the extent to which their voltage sensing mechanisms are conserved is unknown. Here we show that the voltage-sensor paddle, a motif composed of S3b and S4 helices, can drive channel opening with membrane depolarization when transplanted from an archaebacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
278
6
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(299 citation statements)
references
References 49 publications
13
278
6
2
Order By: Relevance
“…Only small portions of the two domains, e.g. the "paddle" motif of the VS domain and the P loop with most of the transmembrane domains of the pore, could be exchanged between K + channels (Lu et al, 2001;Alabi et al, 2007). These results led to the conclusion that membrane modules have coevolved so intimately in Kv proteins that it is impossible to exchange them entirely without losing the function of the chimeric channels.…”
Section: Viral K + Channels Are Ideal For Building More Complex and Mmentioning
confidence: 99%
“…Only small portions of the two domains, e.g. the "paddle" motif of the VS domain and the P loop with most of the transmembrane domains of the pore, could be exchanged between K + channels (Lu et al, 2001;Alabi et al, 2007). These results led to the conclusion that membrane modules have coevolved so intimately in Kv proteins that it is impossible to exchange them entirely without losing the function of the chimeric channels.…”
Section: Viral K + Channels Are Ideal For Building More Complex and Mmentioning
confidence: 99%
“…[9][10][11] In fact, VSDs exist as independent gene products, coupled to other kinds of proteins, as demonstrated by the voltage-sensitive phosphatases 12 and can even mediate proton transport, as shown in the voltage-sensitive proton channels. 13,14 As diverse as the functions of VSDs may be, they all work by converting electrostatic energy into conformation changes and it seems that the basic mechanism of voltage sensing is the same.…”
Section: Introductionmentioning
confidence: 99%
“…S4 of both mVSOP and Hv1 contain three arginines (R201, R204, and R207 in mVSOP, which are equivalent to R205, R208, and R211 in Hv1) that correspond to positively charged amino acids in S4 of voltagegated ion channels. Moreover, the area called the "paddle region," which is comprised of parts of S3 and S4 in Hv1, can replace the corresponding region in voltage-gated potassium channels without affecting voltage-dependent ion channel activity, indicating that a paddle motif-like structure is conserved among Hv and voltagegated potassium channels (20).Earlier studies by ourselves and others showed that Hv channels form dimers via their cytoplasmic regions (21−23), although monomeric Hv channels lacking their cytoplasmic regions remain functional and exhibit robust Hv channel activity (21,22). This motivated us to further define the minimum unit for Hv channel activity.…”
mentioning
confidence: 99%